Parent and Teacher Depictions of Gender Gaps in Secondary Student Appraisals of Their Academic Competences - Sáinz, Milagros; Fàbregues, Sergi; Solé, Jordi (Frontiers in Psychology, 2020)
The present study examines a group of secondary teachers’ and parents’ appraisals of gender gaps in secondary students’ self-assessment of competence in Science, Technology, Engineering, and Mathematics (STEM) and non-STEM domains. Eight focus groups with 39 parents and 34 secondary teachers were conducted for this purpose. In light of the observed gender gaps in students’ performance and self-perception of ability in the different subject areas, the participants were particularly surprised by girls’ underestimation of their abilities in STEM subjects, compared with boys’ tendency to overestimate their abilities in STEM. Most participants agreed on the need for measures to combat these inaccuracies and discussed possible causes. Some participants associated these gender disparities in students’ self-assessment of ability with gender gaps in their choices of subject areas and occupations. The role played by school, teachers, families, and other socialization agents in reinforcing gender stereotypes about academic competence was also discussed in most of the focus groups. Interestingly, some teachers questioned why gender attainments obtained in schools do not serve as an example when it comes to neutralizing the sexism and gender inequality messages offered by the media and society. Likewise, technology teachers proposed changes in school practices to close gender gaps in certain areas (i.e., boys’ appropriation of the playground, or the reproduction of gender roles in the classroom). Few parents acknowledged their unconscious reproduction of gender roles and stereotypes in raising their children.